2012
DOI: 10.1177/0267659112437776
|View full text |Cite
|
Sign up to set email alerts
|

The role of asymmetry and the nature of microembolization in cognitive decline after heart valve surgery: a pilot study

Abstract: Our objective was to determine the role of asymmetry and the nature of microembolization on postoperative cognitive decline in patients who had undergone heart valve surgery. Continuous transcranial Doppler ultrasound was intraoperatively used for both middle cerebral arteries in 13 right-handed heart valve surgery patients to detect microembolization. The Trail Making Test A and B, Memory with 10/30 s interference, the Digit Span Test and Phonemic Fluency were performed preoperatively, at discharge and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Although the attention network has been thought to be right-lateralized, activation in circumscribed regions in left frontal and parietal areas has been attributed to several subdomains of visual search (Weidner et al 2009). Additionally, performance in the TMT has been found to be specifically affected by hypoperfusion of the left hemisphere, which is in line with our finding of the left CH4 region specifically affecting TMT performance Zanatta et al 2012).…”
Section: Effects Of Nbm Volumes On Attention and Executive Functionssupporting
confidence: 91%
See 1 more Smart Citation
“…Although the attention network has been thought to be right-lateralized, activation in circumscribed regions in left frontal and parietal areas has been attributed to several subdomains of visual search (Weidner et al 2009). Additionally, performance in the TMT has been found to be specifically affected by hypoperfusion of the left hemisphere, which is in line with our finding of the left CH4 region specifically affecting TMT performance Zanatta et al 2012).…”
Section: Effects Of Nbm Volumes On Attention and Executive Functionssupporting
confidence: 91%
“…During inspection of partial regression plots we found evidence for a quadratic rather than a linear effect of the left CH4 volume on performance in the TMT Part A and B. Referring to a report on the finding that hypoperfusion of the left hemisphere is associated with postoperative low performance in the Trail-Making-Test, we considered a focus on this subregion appropriate Zanatta et al 2012). Holley et al (1995) modulated the activity of cholinergic basal forebrain cells in a rat model of sustained attention using a GABA A -receptor antagonist.…”
Section: Discussionmentioning
confidence: 86%
“…Further, we demonstrate how the existing analysis methods can be used to study individual and population differences in cerebral vasculature at the level of the entire vasculature, specific arteries or single branches. Age-related changes, hemispheric lateralization, and gender-related difference in cerebral circulation may all be important risk factors in cerebrovascular disorders (Zanatta et al, 2012; Zurada et al, 2011). For instance, increase in tortuosity of right arterial trees during normal aging may have clinical implications (Zurada et al, 2010, 2011), while higher rate of subarachnoid hemorrhages in women may be caused by hormonal differences (Ghods et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1 Cognitive decline at discharge from the hospital, namely, short-term POCD, is mainly due to procedure-related factors, such as cerebral hypoperfusion and microembolization associated with the duration of cardiopulmonary bypass (CPB). 2 Conversely, long-term (≥1 year) POCD is more likely to be ascribed to patient- rather than procedure-related factors, such as low educational level, pre-existing cerebrovascular disease, cognitive impairment or dep-ression. 1,3 Among these factors, it has been shown that pre-existing cognitive impairment plays a key role in long-term cognitive decline after surgery.…”
mentioning
confidence: 99%
“…The latter period of time is particularly interesting given that there is evidence that it is influenced by both patient- and procedure-related factors. 2,5 Importantly, the three-month follow-up is also critical for postsurgical recovery given that it has been indicated as the first time interval for post-convalescent assessment relevant to postoperative cognitive outcome. 6 Therefore, after local ethics committee approval, we examined the influence of such factors on cognitive decline at middle-term follow-up in 79 patients who were admitted for first-time elective cardiac surgery with CPB and gave their informed written consent (for the characteristics of the sample, see Ref.…”
mentioning
confidence: 99%